PERLINDUNGAN HUKUM TERHADAP EKSPRESI BUDAYA TRADISIONAL DALAM PERSPEKTIF UNDANG UNDANG HAK CIPTA - Hendra Djaja (University of Merdeka Malang, 2016)
According to the statistics year 2010 in Indonesia there are more than a thousand nations across Nusantara sothat Indonesia is very rich in diversity of the traditional cultural expressions.The traditional cultural expressions are “intangible culture creation” an ancestral estate that must be maintained, maintained, developed andprotected from exploitation and unilateral claim a foreign country or misappropriation. The creator of thework of cultural expression generally not recognized, so that an obligation to protect the traditional culturalexpressions especially being on the state as copyright holders and to indigenous as caretaker the origin of thebirth of creation culture it. jika ownership of intellectual property in regime trips is individual so that inprotection the traditional cultural expressions ownership of their rights are communal namely to be sharedindigenous caretaker creation traditional culture concerned. As the holder of the power of the traditionalcultural expressions, the government is given the right of the management or a right economic exploitation(economic rights) an expression of the traditional culture of rights moralnya while (moral rights), remain onthe community. The law enforcement abuse of the traditional cultural expressions existing during this is lessexhilarating. Several factors thought to cause the ineffectiveness of law enforcement abuse by foreign partiesclaiming unilaterally cultural expression the traditional. Copyright Act Number 28 Year 2014 expected moreeffective in legal protection the traditional cultural expressions.